PENGARUH KOMITMEN ORGANISASIONAL, MOTIVASI INTRINSIK,DAN MOTIVASI EKSTRINSIK TERHADAP KINERJA DOKTER (Studi pada Dokter Rumah Sakit Umum Daerah Ulin Banjarmasin) - Agustina Rahmah; Ahmad Alim Bachri; Anna Nur Faidah (Universitas Lambung Mangkurat, 2013)
This research aimed to know and analyse influence of organizational commitment, intrinsic motivation, and extrinsic motivation either partial and simultaneus on doctor’s performance in Ulin hospital region general service office Banjarmasin. The purpose of this study is explanatory research. Research sample stipulating technique that used stratified proporsional random sampling, got research sample as much as 112 respondents from population 157 person. Data analysis with multiple linear regression analysis, uses SPSS 17.0 program. Result of F test and t test indicate that organizational commitment, intrinsic motivation, and extrinsic motivation have positive and significant influence on doctor’s performance either through partial and simultaneous. Intrinsic motivation have biggest influence on doctor’s performance, caught up by extrinsic motivation and organizational commitment